An investigation on using teaching media in teaching speaking skill - Fitri Marhamah; Asnawi Muslem; Saiful Marhaban (English Education Journal, 2022)
Teaching media is a mode and learning messages to students that can help teachers to improve students’ learning achievement. This study aimed at finding kinds of the teaching media used by teacher in teaching speaking skill and the obstacles that she encountered in using teaching media. This study is a qualitative study. There were one teacher and one online class meeting involved in this study. To collect the data, the researcher employed observation via Zoom Cloud Meeting recording and interview. The result of the study indicates that there are 8 of teaching media which are generally used by the teacher, comprising: Zoom application, WhatsApp group, Microsoft word and Microsoft PowerPoint, video, YouTube, whiteboard, and course book. The teacher faced the obstacles toward the difference background of students’ ability, the number of the students, the availability of network, and the teacher’s less attention in using teaching media. In short, the teacher should consider the appropriateness of teaching materials to the students’ level of intelligence because it will help them to understand the material successfully.